Exposure and Exercise Training in Hypoxic Conditions as a New Obesity Therapeutic Modality: A Mini Review - Park, Hun-Young (J Obes Metab Syndr, 2018)
Obesity is an important health problem caused by positive energy balance. Generally, low calorie dietary intake combined with regular exercise is the most common modality to lose bodily fat in obese people. Although this is the first modality of choice for obesity treatment, it needs to be applied to obese patients for at least 12 weeks or more and it does not provide consistent results because it is difficult to suppress increased appetite due to exercise. Recently, many researchers have been applying hypoxic conditions for the treatment of obesity, as many studies show that people residing in high altitudes have a lower percentage of body fat and fewer obesity-related illnesses than people living at sea level. Hypoxic therapy treatment, including hypoxic exposure or hypoxic exercise training, is recommended as a way to treat and prevent obesity by suppression of appetite, increasing basal metabolic rate and fat oxidation, and minimizing side effects. Hypoxic therapy inhibits energy intake and appetite-related hormones, and enhances various cardiovascular and metabolic function parameters. These observations indicate that hypoxic therapy is a new treatment modality for inducing fat reduction and promoting metabolic and cardiovascular health, which may be an important and necessary strategy for the treatment of obesity. As such, hypoxic therapy is now used as a general medical practice for obesity treatment in many developed countries. Therefore, hypoxic therapy could be a new, practical, and useful therapeutic modality for obesity and obesity-related comorbidities.